Studentmobilitet for kvalitet i høyere utdanning - Ane Bergersen; Prisca Bruno Massao (Nordic Journal of Comparative and International Education)
Student mobility has long been a desired form of internationalization in higher Education in Norway. Previous research shows increased personal, professional and intercultural competencies after their stay in Zambia and Tanzania. In this paper, we shed light on how cooperation partners in Zambia and Tanzania, through equal knowledge exchange and positions, can contribute to strengthening the quality of student mobility from Norway. We conducted qualitative interviews with six coordinators in Zambia and Tanzania to learn from their reflections regarding student mobility from Norway. The themes discussed in the interviews are student mobility, global justice and de-colonial awareness. The theoretical framework is critical pedagogy and de-colonialization, which analyses power, positions, and pluriversity in international cooperation. Our findings indicate the reproduction of colonial structures and more academic responsibility to colleagues in Zambia and Tanzania, and they suggest adequate preparations with particular learning outcomes to increase the quality of student mobility.